Stability of push–pull small molecule donors for organic photovoltaics: spectroscopic degradation of acceptor endcaps on benzo[1, 2-b:4, 5-b′]dithiophene cores. Issue 34 (19th August 2019) - Watts, Kristen E.; Nguyen, Trung; Tremolet de Villers, Bertrand J.; Neelamraju, Bharati; Anderson, Michael A.; Braunecker, Wade A.; Ferguson, Andrew J.; Larsen, Ross E.; Larson, Bryon W.; Owczarczyk, Zbyslaw R.; Pfeilsticker, Jason R.; Pemberton, Jeanne E.; et al.
Abstract : Degradation pathways of small molecule donors for organic photovoltaics are shown to be dependent on chemical traits and not just redox properties. Abstract : High efficiency organic photovoltaic devices have relied on the development of new donor and acceptor materials to optimize opto-electronic properties, promote free carrier generation, and suppress recombination losses. With single junction efficiencies exceeding 15%, materials development must now target long-term stability. This work focuses on the photobleaching dynamics and degradation chemistries of a class of small molecule donors inspired by benzodithiophene terthiophene cores (BDT-3T) with rhodanine endcaps, which have demonstrated 9% efficiency in single junction devices and >11% in ternary cells. Density functional theory was used to design three additional molecules with similar synthetic pathways and opto-electronic properties by simply changing the electron accepting endcap to benzothiazoleacetonitrile, pyrazolone, or barbituric acid functional groups. This new class of semiconductors with equivalent redox properties enables systematic investigation into photobleaching dynamics under white light illumination in air. Degradation chemistries are assessed via unique spectroscopic signatures for the BDT-3T cores and the endcaps using photoelectron spectroscopies. We show that the pyrazolone undergoes significant degradation due to ring opening, resulting in complete bleaching of the chromophore. The barbituric and rhodanine endcap molecules have moderate stability, while the benzothiazoleacetonitrile group produces the most stable chromophore despite undergoing some oxidative degradation. Collectively, our results suggest the following: (i) degradation is not just dependent on redox properties; (ii) core group stability is not independent of the endcap choice; and (iii) future design of high efficiency materials must consider both photo and chemical stability of the molecule as a whole, not just individual donor or acceptor building blocks.